Stock assessment of Lepturacanthus savala (Cuvier, 1829) along north-west sector of Mumbai coast in Arabian Sea - Rizvi, A F; Desmukh, S K; Chakraborty, S K (Indian Journal of Fisheries, 2016)
Population parameters of Lepturacanthus savala from the trawl and dol net catches from Mumbai waters were estimated based on length frequency data using FiSAT and ELEFAN. The length-weight relationship for pooled data was log W = -7.9652 + 3.6117 log L (r = 0.962). The asymptotic length (L) and growth coefficient (K) were estimated to be 688 mm, and 0.87 year-1, respectively. Based on these growth parameters, the instantaneous total mortality coefficient (Z) during the study period was estimated to be 4.15 year -1. The natural mortality coefficient (M) was 1.30. Hence fishing mortality (F) was 2.85 year -1 for L. savala. The estimated value for the exploitation ratio (E) was 0.68. The recruitment was continuous with two peaks per year. The estimated size of L. savala at 50 percent probabilities of capture was 463 mm. An isopleth diagram was obtained when E = 0.6 and Lc/L = 0.5.